Feasibility, safety and efficacy of human intra-tumoral immuno-therapy. Gustave Roussy's initial experience with its first 100 patients. (September 2022) - Tselikas, Lambros; Dardenne, Antoine; de Baere, Thierry; Faron, Matthieu; Ammari, Samy; Farhane, Siham; Suzzoni, Steve; Danlos, François-Xavier; Raoult, Thibault; Susini, Sandrine; Al Shatti, Nael; Mouraud, Severine; et al.
Abstract: Purpose: Many intratumoural (IT) immunotherapies are currently developed in the clinic with the aim of overcoming primary and secondary resistance and/or to limit on-target/off-tumour toxicities of immune checkpoint targeted therapies. This study aimed to describe the feasibility, safety and efficacy of IT immunotherapy treatments. Design: This retrospective single-centre study included the first 100 consecutive patients enrolled in Gustave Roussy's Human IntraTumoral-ImmunoTherapy (HIT-IT) program. Patient characteristics, target description, image guidance, safety and response according to iRECIST (Response Evaluation Criteria in Solid Tumours for immunotherapy trials) were recorded. Predictive factors of complications and responses were analysed. Survival was also reported. Results: From 09/2015 to 05/2020, 100 patients had 115 tumours injected during 423 treatment cycles. Most frequent primary tumour arose from the skin (n = 49), digestive track (n = 4) or head and neck (n = 8). Injected tumours' mean diameter was 37 ± 23 mm, and a median number of 4 IT injections per patient (interquartile range:3–5) were performed. Targeted tumours for IT injections were superficial lymph nodes (36.5%), subcutaneous lesions (25.2%), liver tumours (20.9%) and others (17.4% including tumour sites such as deep lymph nodes or lung). Most patients (72%) received systemic immunotherapy in combination with HIT-IT. Procedure- and drug-related adverse events (AEs) occurred in 11.3% and 33.3% of the treatment cycles, respectively. Only 3 procedure-related AEs were grade-3 (0.7%); and no grade-4 or 5 occurred. Among all cycles, 7 grade-3 and 1 grade-5 drug-related AEs were reported. Complete and partial responses were achieved for 5% and 18% of patients, respectively, while stable disease was the best response for 11%. Patients receiving HIT-IT as a 1st-line treatment (24%), or not previously pre-treated with immunotherapy (53%) responded better, p = 0.001 and p = 0.004, respectively. From 1st cycle of IT, 12-month overall progression-free survival and overall survival were 21% (14–31%) and 57% (47–68%), respectively. Conclusions: This retrospective study, conducted on patients with cancer and treated within clinical trials at Gustave Roussy, demonstrates the feasibility and safety of the IT immunotherapy strategy. Graphical abstract: Image 1 Highlights: Image-guided intratumoural immunotherapy is feasible for both superficial and deep lesions. No procedure-related grade 4 or 5 adverse events were observed. A high response rate of injected tumours has been observed.